Serbian & Greek art music : a patch to Western music history - Rōmanou, Kaitē (Intellect, 2009)
Serbian and Greek Art Music is the first ever book in the English language to examine the assimilation and development of western art music in Serbia and Greece during the nineteenth and twentieth centuries. Music education, music life and the creation of the two neighbouring nations since they gained freedom from the Ottomans in the nineteenth century are themes that reverberate through the volume. The book relates the efforts of local musicians to synchronize their musical environment with the West and achieve the inclusion of Serbian and Greek music in western music history, an aim that see.